Analisis Perbandingan Jenis PLTS 200 WP Untuk Mengukur Biaya Instalasi Pada Skala Rumah - Mas Ahmad Baihaqi; Andi Susilo (CV. Sekawan Siji, 2024)
The need for electrical energy is currently increasing in line with technological advances, but the energy supply is still insufficient. There have been many developments of power plants using sunlight. Therefore, this study is to analyze the costs required for planning a 200 Wp PLTS as a renewable energy source. This research was conducted in the Dringu sub-district, Probolinggo district, on Thursday 6 June 2023 at 08.00 - 14.53 WIB. The research begins with data collection of sunlight intensity. The highest light intensity on the first day was recorded at 12:38 WIB was 1622 Lux, the second day the sunlight intensity was recorded at 12:02 WIB was 1607 Lux and the third day the sunlight intensity was recorded at 12:32 WIB was 1606 Lux. With the output power of solar panels that produce 1.18 kWh/Day, the amount that can be generated for one day is Rp. 1,704.75 and in one year is Rp. Rp. 613,708.56. The cost of making a 200 Wp PLTS is Rp. 3,977,000 so that it takes 6.4 years to recover the initial investment costs. The total advantage of using a 200 Wp solar panel is Rp. 15,097,230.56.